On the enhancement of transmission control protocol for the evolving internet - Lu, Xiao. (2011)
With the evolving of the Internet, we have witnessed the emergence of novel network technologies and various kinds of network environments, high speed networks (e.g., OBS network, high speed Ethernet), wireless networks (e.g., ad hoc network and satellite network), wired-cum-wireless networks (e.g., last-hop wireless network (LWN)) and others. TCP, the most popular transmission protocol, which carries most of applications in the Internet ranging from bulk data transmission to web browsing, has been significantly challenged nowadays.